2017
DOI: 10.3310/phr05020
|View full text |Cite
|
Sign up to set email alerts
|

Steps Towards Alcohol Misuse Prevention Programme (STAMPP): a school- and community-based cluster randomised controlled trial

Abstract: BackgroundAlcohol use in young people remains a public health concern, with adverse impacts on outcomes such as health, well-being, education and relationships.ObjectivesTo assess the effectiveness and cost-effectiveness of a combined classroom curriculum and parental intervention on self-reported alcohol use [heavy episodic drinking (HED)] and alcohol-related harms (indicators such as getting into fights after drinking, poorer school performance and trouble with friends and family).DesignA two-arm, cluster ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 112 publications
(157 reference statements)
1
30
0
1
Order By: Relevance
“…It appears that, in an environment where parents often feel helpless regarding their ability to impact adolescent risk taking, strict parental rules may contribute to a reduction in HED, both directly and indirectly via reduced sensation seeking. Prevention interventions that include a parental component aimed at fostering strict parental rules may be a way of promoting a shift in parental rule setting and reducing HED (see, e.g., Koning, van den Eijnden, Engels et al., ; Koning, van den Eijnden, Verdurmen et al., ; McKay et al., ; Sumnall et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It appears that, in an environment where parents often feel helpless regarding their ability to impact adolescent risk taking, strict parental rules may contribute to a reduction in HED, both directly and indirectly via reduced sensation seeking. Prevention interventions that include a parental component aimed at fostering strict parental rules may be a way of promoting a shift in parental rule setting and reducing HED (see, e.g., Koning, van den Eijnden, Engels et al., ; Koning, van den Eijnden, Verdurmen et al., ; McKay et al., ; Sumnall et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The study uses data from a cluster randomized controlled trial examining the efficacy of an alcohol education intervention (McKay et al., ; Sumnall et al., ). Only those pupils randomized to the control group were included in this analysis because of the potential interaction between the intervention and key variables in the model.…”
Section: Methodsmentioning
confidence: 99%
“…Of the previous studies that do exist, they have explored the use of classroom-based curricula and parental interventions as primary prevention with young people. 47 One such is the Steps Towards Alcohol Misuse Prevention Programme trial, 47 which explored the effectiveness of a school and parent alcohol intervention. This trial found a significant reduction in heavy episodic drinking in 12-to 13-year-olds; the intervention was delivered at classroom level and not to individuals.…”
Section: Alcohol Screening Toolsmentioning
confidence: 99%
“…This trial found a significant reduction in heavy episodic drinking in 12-to 13-year-olds; the intervention was delivered at classroom level and not to individuals. 47 The Kids and Adults Together programme trial 48 explored the acceptability of primary school classroom-based activities, family events and a digital versatile disc (DVD) to address the effects of alcohol in 9-to 11-year-olds in Wales as a primary preventative measure. The trial found mixed support from the nine primary schools, with two withdrawing from the study.…”
Section: Alcohol Screening Toolsmentioning
confidence: 99%
“…In England, an alcohol abuse prevention program (STAMPP (Steps Towards Alcohol Misuse Prevention Programme)) was created, combining the school curriculum on alcohol and various interventions. The results of the study showed that students developed positive behavioral changes with respect to alcohol, but preventive programs do not reduce the harmful effects of alcohol on young people [13]. Parents also have an influence on alcohol consumption.…”
Section: Introductionmentioning
confidence: 93%